Cognition: A Study in Mental Economy. Issue 2 (6th February 2023) - Wojtowicz, Zachary; Loewenstein, George
Abstract: In this letter, we argue that an economic perspective on the mind has played—and should continue to play—a central role in the development of cognitive science. Viewing cognition as the productive application of mental resources puts cognitive science and economics on a common conceptual footing, paving the way for closer collaboration between the two disciplines. This will enable cognitive scientists to more readily repurpose economic concepts and analytical tools for the study of mental phenomena, while at the same time, enriching our understanding of the modern economy, which is increasingly driven by mental, rather than physical, production.